2021
DOI: 10.1039/d1cp03608d
|View full text |Cite
|
Sign up to set email alerts
|

Competitive tetrel bond and hydrogen bond in benzaldehyde–CO2: characterization via rotational spectroscopy

Abstract: The rotational spectrum of the 1:1 benzaldehyde-CO2 complex has been investigated by pulsed-jet Fourier transform microwave spectroscopy complemented with quantum chemical calculations. Two isomers, both characterized by one C···O tetrel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…[8][9][10][11][12] Both physical and chemical sorption of CO 2 represent a practical interest. [13][14][15][16][17][18] The current chemisorption solutions are preferentially based on the formation of a carbon-nitrogen covalent bond (viz., alkyl amines and derivatives) and strong oxygen-metal ionic bonds (viz., carbonate looping). [19][20][21] In turn, the physical sorption of CO 2 relies on the electrostatic attraction between the oxygen atoms of CO 2 and the electrondeficient interaction centers of the scavenger or the carbon atom of CO 2 and the electron-rich interaction centers of the scavenger.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Both physical and chemical sorption of CO 2 represent a practical interest. [13][14][15][16][17][18] The current chemisorption solutions are preferentially based on the formation of a carbon-nitrogen covalent bond (viz., alkyl amines and derivatives) and strong oxygen-metal ionic bonds (viz., carbonate looping). [19][20][21] In turn, the physical sorption of CO 2 relies on the electrostatic attraction between the oxygen atoms of CO 2 and the electrondeficient interaction centers of the scavenger or the carbon atom of CO 2 and the electron-rich interaction centers of the scavenger.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, before the term of TB, 20–22 the rotational spectroscopic study of the CO⋯CO TB complex has been reported in the formaldehyde homodimer which has a C⋯O distance of 2.98 Å, 23 shorter than the sum (3.22 Å) of van der Waals radii of C and O atoms. 24 Recently, the donor of TB was further extended to molecules containing the CO moiety such as OCS, 25 CO 2 , 26–29 aldehydes 30,31 and benzophenone. 32 The sp 3 -C can also act as a TB donor, as disclosed in the rotational study of the 3,3-dimethyl-tetracyanocyclopropane-tetrahydrofuran complex.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 has a dual role in the link with formic acid 45 and acrylic acid 46 through a dominant O−H•••OC HB and a secondary C•••O TB. On the contrary, with benzaldehyde (BA), 47 formaldehyde (H 2 CO), 48 formamide (FM), 49 propylene oxide, 50 ethylene oxide, 51 methanol, 52 isopropylamine, 53 difluoromethane, 54 1,1difluoroethylene, 55 and trifluoroethylene, 56 47 This further emphasizes the impact of substituents on interaction topologies by changing the electronic structures of partner molecules. The introduction of side alkyl chains has been recognized as an efficient strategy for tuning self-assembly, 57 liquid crystals, 58 molecular solubilities, 59 and gas sorption properties, 60,61 wherein the alkyl chain length modulates the propensity to form intermolecular interactions and stacks.…”
mentioning
confidence: 99%
“…There has been a long-lasting effort to qualitatively and quantitatively understand the intermolecular interactions of CO 2 through rotational spectroscopic investigations. With the oxygen lone pairs and a π* antibonding orbital (or π-hole) associated with the carbon atom, CO 2 can act as an electron donor or an electron acceptor, interacting with different partner molecules . As a rough conclusion, the interaction preference of CO 2 with linear HX (X = F, Cl, Br, or CN) mainly depends on the electronegativity of X (F > Cl > CN > Br).…”
mentioning
confidence: 99%
See 1 more Smart Citation